Aqil Water Customer Data Collection System With Website Technology Using Design Thinking Method - Romensyah, Erwin; Fitriani, Wirda; Muhammad Amin (Cattleya Darmaya Fortuna, 2025)
This study focuses on the design and development of a web-based customer data collection system for Aqil Water, aiming to address inefficiencies arising from manual data management. The system was developed using the PHP programming language and implemented with a MySQL database via XAMPP phpMyAdmin. By adopting the Design Thinking method, the system was designed to be user-oriented, providing digital forms, structured data organization, and interactive dashboards. Key features include customer data input, item and unit management, transaction records, and gift tracking for loyalty programs. The system significantly improves data accuracy, accessibility, and operational efficiency. Despite its successful implementation, the system currently has limitations in accessibility, which suggests the need for future development into a mobile-based and online-accessible platform